The effects of political, economic and social events on the Order of Freemasons in South Africa, with some reference to the movement for the formation of a United Grand Lodge, 1772-1961 - Cooper, A. A. (Alan Amos) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1983.